Bimanual Skill Learning after Transcranial Direct Current Stimulation in Children with Unilateral Cerebral Palsy: A Brief Report. (3rd October 2019) - Nemanich, Samuel T.; Rich, Tonya L.; Gordon, Andrew M.; Friel, Kathleen M.; Gillick, Bernadette T.
ABSTRACT: Bimanual skills are important for goal-oriented activities. Children with unilateral cerebral palsy (UCP) have deficits in unimanual and bimanual motor control and learning. The application of non-invasive brain stimulation with existing motor training may further promote motor learning; however, the effects of stimulation on bimanual learning have not been examined. Here, we assessed the performance of a novel bimanual skill (modified Speed Stacks task) in eight children with UCP before, during, and after a combined motor training and brain stimulation intervention. Participants received 10 days (120 min/day) of goal-oriented bimanual therapy combined initially with transcranial direct current stimulation (tDCS, 20 min/day). Results showed task improvement tapered (p < 0.001) during and after the intervention and task variability decreased in 6/8 participants, indicating the potential impact of novel rehabilitation to improve skill learning in children with UCP. Future work is required to understand how both tDCS and bimanual training contribute to learning bimanual tasks.